Peripheral blood involvement in non-Hodgkin's lymphoma detected by clonal gene rearrangement as a biological prognostic marker. - Hiorns, L. R. (Nature Publishing Group, 1994)
Peripheral blood from 67 patients with non-Hodgkin's lymphoma was examined at initial diagnosis for the presence of circulating lymphoma cells by DNA hybridisation using immunoglobulin and T-cell receptor gene probes. Clonal gene rearrangement was found in 31% (21/67) of patients and correlated with clinical stage, histological grade and bone marrow involvement. Clinical stage and the presence of lymphoma cells in peripheral blood were prognostic factors for progression-free survival in all patients on univariate analysis, but the detection of lymphoma cells was not independent of stage. It was also not a significant predictor for survival. In patients with intermediate- and high-grade lymphoma, the detection of lymphoma cells in peripheral blood was a significant prognostic factor for progression-free survival (PFS) and survival only on univariate analysis. The 3-year PFS was 17% in patients with circulating lymphoma cells compared with 75% if these were absent (P < 0.05). The presence of lymphoma cells in peripheral blood is associated with extensive disease and may be a biological marker of poor disease control. Sensitive techniques of detection should form part of large prospective studies in non-Hodgkin's lymphoma.